Pengaruh Dimensi Saluran Masuk pada Scrap Aluminium Sand Casting Pulley terhadap Kekerasan, Ketangguhan dan Struktur Mikro - Sumpena; Hb. Sukarjo (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2016)
The purpose of this study for determine influence size of the inlet to the hardness, toughness and microstructure pulley with casting mold sand raw materials aluminum scrap. The smelting process using crucible furnace. Sand molds be made 3 kinds of different inlets, each inlet same was made 4 sand molds. Hardness testing is done by using the Vickers hardness test. the load to pressure 100 gf, the time to pressure 5 seconds. Toughness testing with use standard ASTM D256-03 machine test impact charpoy. Observation of microstructure was observed on each specimen by using an optical microscope. The hardness test results show that hardness value of the highest on the dimensions of the inlet height 6 mm is 64.4 VHN while the lowest value to the dimensions of the inlet height 5 mm is 60.96 VHN. The toughness test results show that toughness value from the three specimens almost the same is 0.057 joules / mm2; 0.0565 joule / mm2 and 0.0565 joules / mm2. While the structure micro of castings with high dimensional inlet 5 mm and 7 mm occurred structure micro which is almost the same, while the dimensions of the inlet height 6 mm has a spread of Fe, Si and Mg is more evenly distributed.